Meiobenthos Community as a Description of Environmental Changes at Losari Beach, Makassar - Ahmad Hasyim; Muh. Sri Yusal; Syamsuri Syamsuri; Hasria Alang (Postgraduate, University of Mataram, 2023)
This research aims to describe the ecological values of meiobenthos as a bioindicator of water quality at Losari Beach, Makassar. The sampling method used was the purposive sampling method. The determination of the research location was also based on previous research which described the coastal location of Losari Beach as being polluted by chemicals and dangerous metals. The research data were then analyzed statistically to calculate meiobenthos density, diversity index, and uniformity index. The research results showed that the abundance of meiobenthos found during the research was 66946 indv/m2, consisting of 12 phyla and 91 species/genus. The stations at the mouth of the Tallo River, Jeneberang River, and Tanjung Merdeka are research stations that have high abundance. The phylum oligochaeta, ostracoda, tunicata, and ciliophora are phyla with high abundance compared to other phyla. Based on the research results, it was concluded that this phylum has a high level of adaptation to the entry of various pollutants into water bodies. The diversity and uniformity index shows that the meiobenthos types in Losari are classified as having a high and even diversity index. The dominance index also shows that no single meiobenthos type is dominant, except for those in the reclamation project area. Temperature, current speed, depth, brightness, salinity, pH, DO, seawater nitrate, and seawater phosphate have a correlation or relationship with the abundance of meiobenthos on Losari Beach, Makassar.